OPPORTUNITIES FOR STUDENTS IN MATHEMATICS TO MOTIVATE THEIR SCIENCE - Murod Barakaev , Abduvali Shamshiev , Ahmadjon Axlimirzaev , Sherzodbek Ermatov, Dilmurod Hojiev (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the opportunities to motivate students to learn mathematics in mathematics lessons, the role of students' thinking skills in the development of mathematics, and the ways to achieve it. It also outlines the role of the math teacher in achieving the intended goal through the formation of student learning activities.